Transformative Learning through AI Powered Text-Based Simulations: Enhancing Problem-Based Learning in Higher Education - Hafizan, Mohamad Naim (International University Carnival on E-Learning IUCEL2025, 2025)
This project introduces an innovative teaching practice that integrates AI-powered text-based simulations into Problem-Based Learning (PBL) to enhance engagement, inclusivity, and deep learning. Implemented in SSP2094 Organization Theory and Design, students assumed the role of consultants solving realistic organizational challenges through dynamic ChatGPT simulations. Unlike static case studies, these simulations generate real-time, adaptive scenarios that allow students to explore multiple decision paths and receive immediate feedback. Findings show enhanced critical thinking, collaboration, problem-solving, and reflective learning. This low-cost, text-based approach bridges theory and practice while ensuring accessibility for diverse learners.